The Learning Strategies Used by EFL Students in Learning English - dinda hartina mega; Asih Santihastuti; Eka Wahjuningsih (IJEE (Indonesian Journal of English Education), 2019)
ABSTRACTThis research was aimed to focus on the most frequently used strategy by the successful and unsuccessful senior high school students and describe the difference of strategy used by them. This was a survey design with a questionnaire as the instrument. The participants were 40 students consisting of 20 successful students and 20 unsuccessful students of tenth grade in SMAN 2 Jember. The writer distributed SILL questionnaires to observe their Language Learning Strategy (LLS) based on Oxford (1990), which covers six categorizes of strategies namely cognitive, metacognitive, memory-related, compensatory, affective, and social. The statistical analysis showed that metacognitive became the most frequently learning strategy used by successful students in scale of high use, while the unsuccessful students were medium users of cognitive strategy. It also indicated successful learners employed all six categorizes of strategies in a highly frequencies than the unsuccessful ones. This makes the assumption that successful students have the ability to plan clear goals, control, review, and evaluate their learning rather than unsuccessful students who focus more on the way they think, memorize, summarize, and repeat the learning.ABSTRAKPenelitian ini bertujuan untuk fokus pada strategi yang paling sering digunakan oleh siswa SMA yang sukses dan kurang sukses serta menggambarkan perbedaan strategi yang digunakan oleh mereka. Penelitian ini merupakan penelitian survey dengan instrument berupa kuesioner, sedangkan tanggapan siswa dalam memilih strategi dibahas secara deskriptif. Partisipan adalah 40 siswa yang terdiri dari 20 siswa yang sukses dan 20 siswa yang tidak sukses dari kelas sepuluh di SMAN 2 Jember. Penulis membagikan kuesioner SILL untuk mengamati Language Learning Strategy (LLS) atau strategi pembelajaran bahasa mereka berdasarkan teori Oxford (1990, yang dikategorikan menjadi enam macam strategi, yaitu kognitif, metakognitif, memori, kompensatori, afektif, dan sosial. Menurut hasil statistic metacognitive menjadi strategi pembelajaran yang paling sering digunakan oleh siswa yang sukses dalam skala tinggi, sedangkan siswa yang kurang sukses adalah pengguna menengah dari strategi kognitif. Ini juga menunjukkan bahwa siswa yang sukses menggunakan keenam kategori strategi dalam frekuensi yang sangat tinggi daripada yang kurang sukses. Ini membuat asumsi bahwa siswa yang sukses memiliki kemampuan untuk merencanakan tujuan yang jelas, mengendalikan, meninjau, dan mengevaluasi pembelajaran mereka daripada siswa yang kurang sukses, yang lebih fokus pada cara mereka berpikir, menghafal, merangkum, dan mengulangi pembelajaran. How to Cite: Sartika,  D. H. M., Santihastuti, A., Wahjuningsih, E. (2019). The Learning Strategies Used by EFL Students in Learning English. IJEE (Indonesian Journal of English Education), 6(1), 10-20. doi:10.15408/ijee.v6i1.12111